Lack of Association of C677T Methylenetetrahydrofolate Reductase Polymorphism with Breast Cancer Risk in Mali. (17th January 2023) - Diakite, Brehima; Kassogue, Yaya; Maiga, Mamoudou; Dolo, Guimogo; Kassogue, Oumar; Holl, Jane L.; Joyce, Brian; Wang, Jun; Cisse, Kadidiatou; Diarra, Fousseyni; Keita, Mamadou L.; Traore, Cheick B.; et al.
Abstract : Methylenetetrahydrofolate reductase (MTHFR) plays a major role in the metabolism of folates and homocysteine, which in turn can affect gene expression and ultimately promote the development of breast cancer. Thus, mutations in the MTHFR gene could influence homocysteine, methionine, and S-adenosylmethionine levels and, indirectly, nucleotide levels. Imbalance in methionine and S-adenosylmethionine synthesis affects protein synthesis and methylation. These changes, which affect gene expression, may ultimately promote the development of breast cancer. We therefore hypothesized that such mutations could also play an important role in the occurrence and pathogenesis of breast cancer in a Malian population. In this study, we used the PCR-RFLP technique to identify the different genotypic profiles of the C677T MTHFR polymorphism in 127 breast cancer women and 160 healthy controls. The genotypic distribution of the C677T polymorphism in breast cancer cases was 88.2% for CC, 11.0% for CT, and 0.8% for TT. Healthy controls showed a similar distribution with 90.6% for CC, 8.8% for CT, and 0.6% for TT. We found no statistical association between the C677T polymorphism and breast cancer risk for the codominant models CT and TT p > 0.05 . The same trend was observed when the analysis was extended to other genetic models, including dominant ( p  = 0.50), recessive ( p  = 0.87), and additive ( p  = 0.50) models. The C677T polymorphism of MTHFR gene did not influence the risk of breast cancer in the Malian samples.